Immunological approaches to embryonic development and differentiation. - Moscona, A. A. (Aron Arthur), 1922-2009; Monroy, Alberto; Friedlander, Martin (Current topics in developmental biology, 1979)
CURRENT TOPICS DEVELOPMENTAL BIOLOGY V13.